2021
DOI: 10.1021/acs.cgd.1c00089
|View full text |Cite
|
Sign up to set email alerts
|

An Organosuperelastic Mechanism with Bending Molecular Chain Bundles

Abstract: Specific kinds of alloys, so-called shape-memory alloys (SMAs), show superelasticity. Their mechanism has been known as slight atomic rearrangement by keeping relative positional relationships. Contrary to this, not only molecular rearrangement but also orientational and conformational changes are involved in superelasticity in molecular single crystals. Herein, we investigate superelasticity correlated with molecular bending in a crystal formed by a one-dimensional hydrogen-bonding supramolecular chain of pim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The rotation angle was measured graphically from the single-crystal X-ray structure. The molecular movement is completely different from that in superelastic behavior: i.e., bending of PA by conformational change of the alkyl group causing a reversible polymorphic phase transition between thermally stable modification III and metastable modification II at ambient temperature . There are no strong hydrogen bonds across the twinning interface.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The rotation angle was measured graphically from the single-crystal X-ray structure. The molecular movement is completely different from that in superelastic behavior: i.e., bending of PA by conformational change of the alkyl group causing a reversible polymorphic phase transition between thermally stable modification III and metastable modification II at ambient temperature . There are no strong hydrogen bonds across the twinning interface.…”
Section: Resultsmentioning
confidence: 93%
“…In Figures 1e,f bending of PA by conformational change of the alkyl group causing a reversible polymorphic phase transition between thermally stable modification III and metastable modification II at ambient temperature. 42 There are no strong hydrogen bonds across the twinning interface. A molecular electrostatic potential map of PA (Figure S4) confirmed that only relatively weak intermolecular interactions (very weak hydrogen bonding and dispersion forces) are possible across the twin plane.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ferroelastic behaviors are also caused by mechanically induced polymorphic transitions (pFE) at a specific temperature range, leading to another type of SME based on pFE. 24,25,29,86…”
Section: Deformability Of Organic Crystals By Mechanical Twinningmentioning
confidence: 99%
“…The relationship is achieved not by an actual molecular rotation of 180°but by small molecular movements of a (super)molecule having a pseudo-twofold rotation symmetry element. The movements are an orientational rotation of a rigid molecule, 70,71 flipping of phenyl rings 62 or cyclohexyl rings, 63 chain rotation of an alkyl chain, 29,65 or rotation of functional groups 68 in conformationally flexible molecules, and rotation of guest molecules in a host framework. [15][16][17] The movements can be reduced in a crystal having two or more crystallographically independent molecules (Z′ >1) (Fig.…”
Section: X-ray Crystallographic Approachmentioning
confidence: 99%
See 1 more Smart Citation